Multidimensional and Physical Frailty in Elderly People: Participation in Senior Organizations Does Not Prevent Social Frailty and Most Prevalent Psychological Deficits - Sacha, Magdalena; Sacha, Jerzy; Wieczorowska-Tobis, Katarzyna (Frontiers in Public Health, 2020)
Purpose: The study explores how the involvement in community-based senior organizations affects the prevalence of multidimensional and physical frailty among community dwelling elderly people. Materials and Methods: The group of 1,024 elderly people (270 males) over the age of 65 years (mean age 72.6 ± 6.3 years; range 65–93 years) took part in this study. The subjects completed a questionnaire regarding multidimensional (i.e., the Tilburg Frailty Indicator, TFI) and physical frailty (i.e., the FRAIL scale), as well as factors associated with frailty and participation in senior organizations. Results: The prevalence of multidimensional frailty (if at least 5 points in the TFI) was 54.6%, and the prevalence of physical frailty (if at least 3 points in the FRAIL scale) and a non-robust status (if any point in the FRAIL scale was positive) was 6.3 and 52.9%, respectively. The most prevalent frailty deficits were missing other people (66.6%), feeling nervous or anxious (65.9%), and feeling down (65.5%). Members of senior organizations presented a lower prevalence of multidimensional and physical frailty comparing with non-members. This was mainly caused by a lower prevalence of physical deficits and problems with memory; however, the prevalence of social deficits was similar in both groups. Senior organizations had no influence on the most widespread frailty deficits, i.e., missing other people, feeling nervous or anxious, and feeling down. Conclusions: Multidimensional frailty and physical non-robust status are common among people over the age of 65 years. Participation in senior organizations is associated with lower risk of physical frailty; however, it has no effect on social frailty and the most prevalent psychological deficits. This information has important implications for practical management with senior problems and may influence community strategies concerning elderly people.